ANALISIS KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN BUKU CERITA FIKSI PADA SISWA KELAS I - Teni Okty Handayani; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading is a major aspect of language skills, especially in the world of education. Early reading activities have been introduced from the elementary education level starting from grade I, but there are still many students who are not fluent in reading. Therefore, a study was conducted aimed at determining the reading ability of grade I students, and the effectiveness of using fiction story books on students' reading abilities at SDN Padarek III. This study used a qualitative analysis method with observation and interview techniques. The results of the study showed that many of the reading abilities of grade I students at SDN Padarek III were still not fluent in reading, but after using fiction story books, students became enthusiastic in learning. This proves that fiction story books are effective in learning to improve early reading abilities in grade I students and have a positive impact on students.